Respon Pertumbuhan dan Produksi Jamur Tiram Putih (Pleurotus ostreatus) Terhadap Berbagai Media Serbuk Kayu dan Pemberian Pupuk NPK - M. Fadhil Afief; Ratna Rosanty lahay; Bolonggu Siagian (Universitas Sumatera Utara, 2015)
This research aim toknow kinds of media sawdust most excellent and NPK fertilizer dosage most appropriate for the production of white oyster mushroom (Pleurotus ostreatus). This research was conducted in mushroom oyster mushroom STM 1 Street, District of Johor Medan, Medan with altitude of 25 meters above sea level. The research was conducted from May to September 2014 using A Factorial Complete Randomized Design (CRD) with two factors, namely kinds of media sawdust: M1 (rubber wood), M2 (sawdust kemiri), M3 (sawdust coconut) and NPK: P0 (without fertilizer), P1 (5,6 g NPK/baglog), P2 (11,2 g NPK/baglog), P3 (16,8 g NPK/baglog). Parameters observed were age began to harvest mushrooms, mushroom stalk length, diameter mushroom hood, thick mushroom hood, the amount of hood / cluster, fresh weight mushroom / harvest, fresh weight mushroom / baglog and biological efficiency ratio (BER). Research results show that the kinds of media sawdust significant effect on all parameters. NPK fertilizer significant effect on stalk length parameter mushroom, mushroom hood diameter, fresh weight mushroom / harvest, fresh weight mushroom / baglog, and biological efficiency ratio (BER). Research results show of media rubber wood and without NPK fertilizer is the most excellent treatment in increasing the growth and production of oyster mushrooms.Keywords :White Oyster Mushroom, Media Sawdust, NPK Fertilizer